Akuntabilitas Pelayanan Kesehatan pada Rumah Sakit Umum Daerah Salewangang di Kabupaten Maros - Andayani, Sri Ayu; Setiawati, Budi; Haerana, Haerana (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study purposed to determine accountability in the provision of health services at the Salewangang District General Hospital in Maros Regency. This study  used a qualitative approach with type phenomenology research. Data collection techniques were interview, observation, and documentation. Data analysis  techniques used data reduction, data presentation and drawing conclusions, while the validity of the data used source triangulation, techniques and time. The results of this study showed that the accountability of health services in the Salewangang District General Hospital in Maros Regency viewed from four dimensions, namely: legal accountability and honesty were in line with good and responsible, process accountability had not been categorized well because it had not been running, program accountability had been categorized good and responsible, policy accountability was in line with good and responsible could be seen by the absence of complaints by officers regarding the provisions or policies of the Hospital regarding the implementation.